Pengaruh Leverage dan Struktur Kepemilikan terhadap Kinerja Perusahaan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Alifyyah Putri Ajar Setiadi; Henny Setyo Lestari (J-MAS (Jurnal Manajemen dan Sains), 2022)
Leverage and ownership structure are important aspect on firm performance. Because of that the purpose of this study is to determine the effect of leverage and ownership structure on firm performance. The independent variables in this study are leverage, institutional ownership and foreign ownership. The dependent variable in this study is Firm performance, while the control variable consists of company size and company net income. On the Firm performance, in this study using the measurement of Return on Assets (ROA) and Return on Equity (ROE). This study uses panel data analysis and was conducted by collecting data from 31 manufacturing companies in Indonesia in the period 2016 to 2020. This study found a negative relationship between leverage on firm performance while firm size had a negative relationship with Firm performance with ROE and a positive relationship with ROA. The results of the study of foreign ownership have a positive effect on the performance of companies with ROA and ROE and for the results of net income and institutional ownership have a negative effect on the performance of companies with ROE, while the results of research on net income and institutional ownership have a positive influence on the performance of companies with ROA.